Antioxidant mesoporous Ce-doped bioactive glass nanoparticles with anti-inflammatory and pro-osteogenic activities - Zheng, Kai; Torre, Elisa; Bari, Alessandra; Taccardi, Nicola; Cassinelli, Clara; Morra, Marco; Fiorilli, Sonia; Vitale-Brovarone, Chiara; Iviglia, Giorgio; Boccaccini, Aldo R. (Materials Today Bio, 2020)
Mesoporous bioactive glass nanoparticles (MBGNs) are emerging biomaterials for bone repair/regeneration, considering their favorable pro-osteogenic and proangiogenic activities. To further improve their therapeutic effects, the endowment of MBGNs with additional antioxidant properties is of particular interest to target oxidative stress related to bone remodeling and diseases. To this end, we developed antioxidant cerium-containing MBGNs (Ce-MBGNs) (particle size of 100–300 ​nm) by using a postimpregnation strategy to incorporate Ce, through which the shape, pore structure, and dispersity of the nanoparticles were preserved. The incorporated amount of Ce could be tailored by adjusting the concentration of the Ce precursor solution. When impregnated at a relatively low temperature (20 ​°C), Ce-MBGNs containing either 1.8 or 2.8 ​mol% of Ce were produced, while the formation of by-product cerium oxide nanoparticles (nanoceria) could be avoided. In both developed Ce-MBGNs, the concentration of Ce4+ was higher than that of Ce3+, while the relative molar percentage of Ce4+ was similar (∼74%) in both Ce-MBGNs. The obtained Ce-MBGNs were evidenced to be non-cytotoxic against fibroblasts at the concentration of 1 ​mg/mL. Moreover, the incorporation of Ce into MBGNs significantly reduced the expression of oxidative stress–related genes in macrophages (J774a.1). Particularly in the presence of pro-oxidation agents, Ce-MBGNs could downregulate the expression of oxidative stress–related genes in comparsion with the polystyrene plates (control). When cultured with Ce-MBGNs, the expression of proinflammatory-related genes in macrophages could also be downregulated in comparsion with MBGNs and the control. Ce-MBGNs also exhibited pro-osteogenic activities through suppressing pro-osteoclastogenic responses. The obtained results highlight the great potential of the developed Ce-MBGNs in a variety of biomedical applications, particularly in treating bone defects under inflammatory conditions, considering their antioxidant, anti-inflammatory, and pro-osteogenesis activities.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Anti-inflammatory; Antioxidant; Bioactive particles; Cerium; Pro-osteogenesis; Surface modification